Vetenskapsakademiens Herschel-teleskop: En instrumentbiografi - Kärnfelt, Johan (Slagmark - Tidsskrift for idéhistorie, 2020)
The Herschel Telescope of the Royal Swedish Academy of Sciences: An Instrument Biography The so called Herschel telescope is one of the key items in the artefact collection of the Royal Swedish Academy of Science. The optics was commissioned from William Herschel in England in the mid-1780s and arrived a couple of years later, but the telescope as such was not finished until 1812. Even if it amounted to a considerable investment for the Academy, scientific speaking it turned out to be a total failure. A biographical approach is used to study the instruments shifting roles in the formation of knowledge, from its completion in the early 19th century, until the present era. Since the telescope in its original configuration was unusable, it was firstly rebuild 1842, still without coming to any scientific use, and then reinterpreted as a cultural heritage object. As such, it has since served different roles in several exhibitions contexts.